Vitamin D deficiency in the population of Karachi, Pakistan; A cross-sectional study - Kazmi, S Ali Danish; Mustansir, Ali Asghar; Sheikh, Mareeha; Ahmad Ali, Saad (International Journal of Endorsing Health Science Research, 2020)
Background: Vitamin D deficiency affects over one billion people globally, which results in the progression of severe health consequences and chronic diseases. Literature indicates high rates of vitamin D deficiency in the Pakistani population. Thereby, this current study was aimed to determine the status of vitamin D deficiency in the population of Karachi. Methodology: This descriptive cross-sectional study was conducted during January to December 2017 at the Dadabhoy Institute of Higher Education (DIHE). A total of 1159 healthy individuals aged between 18-72 years were selected for the study. Data was collected through a questionnaire seeking the demographics of the participants. For the quantitative colorimetric immune-enzymatic determination of 25(OH) vitamin D concentrations in the human plasma level, venous blood was collected and was analyzed using a vitamin D Enzyme-Linked Immunosorbent Assay (ELISA) kit. Statistical analysis was carried out using SPSS version 20.0. Results: A total of 1159 participants were included in the study with the mean age of 40.1±15.2 years. It was observed that 59.1% of participants had deficient vitamin D levels, while 22.6% of participants had sufficient vitamin D levels. There was a significant association between gender and vitamin D status (p < 0.05), as the majority of females (68.5%) were vitamin D deficient as compared to males (31.5%). In contrast, no significant association was found between age and vitamin D levels, with the most deficient age group being 18 to 28 years. Conclusion: It is concluded from the study results that vitamin D deficiency was prevalent in the studied population, despite increased exposure to sunlight. The initial screening for early detection and correction of the condition must be considered as an essential component of the national health strategy, as there is a need to detect and combat the burden of vitamin D deficiency in the country.